Association of sugar-sweetened beverage consumption with psychological symptoms among Chinese university students during the COVID-19 pandemic - Wang, Yujie; Bi, Cunjian; Liu, He; Lin, Hongniu; Cai, Ruibao; Zhang, Jie (Frontiers in Psychology, 2022)
Background Mental health of college students has become a public health issue of common concern worldwide. Especially during the COVID-19 pandemic, the problem has become even more acute. The aim of this study was to assess the association between sugar-sweetened beverages (SSB) consumption and psychological symptoms among Chinese college students in order to promote their mental health. Methods The study population was 6,120 college students aged 19–22 years from Anhui, Henan and Xinjiang, China. Basic demographic information, covariates and SSB Consumption data were collected through a self-assessment questionnaire. The “Multidimensional Sub-health Questionnaire of Adolescents” was used to assess the psychological symptoms of college students. The Chi-square test, one-way ANOVA and logistic regression analysis were used to investigate the differences and associations between SSB consumption and psychological symptoms among Chinese college students. Results The detection rate of psychological symptoms among Chinese college students was 8.1%. The detection rate of boys students was 9.4% and that of girls students was 7.1%, and the difference was statistically significant in comparison (χ2-value was 11.08, p < 0.001). After controlling for covariates, Model 2 analysis showed that compared to SSB consumption <2 time/week, college students with SSB consumption ≥2 time/week (OR = 2.96, 95% CI: 2.36, 3.70) had a higher risk of psychological symptoms (p < 0.001). The same trend was found for emotional symptoms, behavioral symptoms, and social adaptation difficulties dimensions. Conclusion There is an association between SSB consumption and the occurrence of psychological symptoms among Chinese college students. Future measures should be taken to reduce both SSB consumption and the incidence of psychological symptoms.